Determination of the LCV (Lead Conductance Value) of Hop Extracts by a simplified version of method EBC 7.6: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Biendl, M. (BrewingScience, 2001)
The EBC Analysis Committee decided to test a simplified version of method EBC 7.6 by a collaborative trial. The new method is allowing for direct conductometric titration of the ether phase instead of preparing a “stock solution”. In winter 1999/2000 a collaborative trial was carried out using three samples of hop extracts with different alpha-acids levels in the range of 20 – 50%. 10 members of the EBC Analysis Committee and 5 members of AHA (Arbeitsgruppe Hopfenanalyse) took part in the collaborative trial.